Influenza vaccination in the COVID-19 era. (September 2020) - Grech, Victor; Borg, Michael
Abstract: Influenza spreads globally annually with significant paediatric and adult attack rates and considerable morbidity, mortality and the exacerbation of extant chronic disease. In the northern and southern hemispheres, outbreaks occur mainly in the respective winter seasons. Influenza vaccination is available but only partially effective. In the absence of a vaccine, in winter, novel coronavirus COVID-19 will also circulate in parallel with seasonal influenza. Thus far it appears that with the current strains of these two viruses, the clinical outcome of co-infection is not significantly worse than infection with COVID-19 alone. However, several strains of influenza circulate, including strains still to come. Similarly, COVID-19 has several strains, with probably more to come. This paper discusses these issues and estimates ideal minimum influenza vaccination coverage based on an estimated influenza Basic Reproduction Number (R0) of 0.9–2.1 so as to obtain herd immunity or approach it. There is a strong argument for attempting near universal population coverage with the annual influenza vaccine leading up to next winter. Highlights: COVID-19 (SARS-CoV-2) is currently a global pandemic. Influenza spreads annually with significant morbidity and mortality. Influenza vaccination is available albeit not completely effective. Next winter both viruses will circulate and co-infect hosts. Universal coverage with influenza vaccine would be ideal next winter.